A value for cephoidal NTU-games - Joachim Rosenmüller (Bielefeld University, Institute of Mathematical Economics (IMW), 2007)
A cephoid is an algebraic ('Minkowski') sum of finitely many prisms in R^n. A cephoidal game is an NTU game the feasible sets of which are cephoids. We provide a version of the Shapley NTU value for such games based on the bargaining solution of Maschler-Perles.
urn:nbn:de:hbz:361-10994
Keywords: 330; Cephoids; Bargaining theory; Bargaining solution; NTU games; NTU value; Transferable Utility Games; Spieltheorie; Verhandlungstheorie; Shapley-Wert; Theorie